Influence of Temperature on the Viscoelastic Behavior and Durability of Flexible Pavements - Omar Ben Charhi; Khadija Baba (Civil Engineering Journal, 2024)
This study meticulously examines the impact of temperature variations on the viscoelastic characteristics of flexible pavements composed of mineral aggregates and bituminous binders. The primary objective is to understand how temperature fluctuations affect the structure and durability of these pavements, designed to withstand traffic loads while absorbing stresses induced by weather conditions. The methodology involves a thorough analysis of a range of temperatures from T1 to T4, assessing their effects on road rutting and the longevity of pavement infrastructure. Through a detailed analytical approach, the research investigates the viscoelastic behavior of bituminous mixes, which display viscous and elastic properties that change with temperature. The findings reveal significant correlations between temperature variations and the performance of flexible pavements, offering insights into their structural resilience and durability under different climatic conditions. This research introduces a novel approach to managing flexible pavement infrastructure by enhancing our understanding of the temperature-induced viscoelastic response. The improvement lies in the precise quantification of temperature impacts, which can inform better maintenance and design strategies for flexible pavements. Ultimately, this leads to more resilient and long-lasting road surfaces, addressing the critical need for durable infrastructure in changing weather patterns. Doi: 10.28991/CEJ-2024-010-07-06 Full Text: PDF